Islamic smart city innovation, concept, application and Shari’ah parameters: a theoretical assessment and technological advancement in artificial intelligence - Adam Sa'ad, Auwal; Abubakar, Adamu; Hasan, Aznan; Abubakar, Usman (Global Journals, 2022)
Abstract- It is the goal of this paper to establish mechanisms for smart cities to include Islamic approaches by interacting with the following components: "Smart Facilities", "Smart Devices", "Smart Governance", "Smart Data", and "Smart People "influence towards the adoption of Islamic smart city concepts, taking into account the wide range of smart city components. Assessment of these variables associated Islamic approach has been presented in this paper. It was revealed that in order to improve the quality of life, a smart city makes use of cutting-edge advance technology and technological tools like sensors and a sensor network, among other things. Furthermore, Smart city adoption in the Muslim world, Muslim communities, or in and around Muslim-majority areas has also been a long-standing quest for ways to improve the quality of life for Muslims. While also taking into consideration the Islamic approach to constructing a smart city, the concept will conserve and promote a more environmentally conscious community.